Responses of reinforced soil retaining walls subjected to horizontal and vertical seismic loadings. Issue 129 (February 2020) - Fan, Cheng; Liu, Huabei; Cao, Jianzhou; Ling, Hoe I.
Abstract: Vertical ground acceleration is a component in an earthquake loading, and in some cases, the vertical to horizontal acceleration ratio (V/H ratio) may be very large. However, the influences of the vertical seismic loading on the responses of reinforced soil retaining walls are still not clear. In this study, a Finite Element procedure was further validated by a large-scale shaking table test subjected to both horizontal and vertical seismic loadings. It was then employed to investigate the seismic responses of two models considering a large range of earthquake loading scenarios. The results showed that the vertical ground acceleration might alter the shear wave propagation in the reinforced soil, but the Arias intensity at the top of the reinforced soil correlated well with the maximum reinforcement load. The vertical seismic loading mostly increased the reinforcement load, but reduced the residual facing displacement. The reduction of lateral facing displacement may have come from the increase of the confining pressure and the change in the far-field lateral displacement due to the vertical seismic loading. Some limitations of the present study are also discussed. Highlights: A FE procedure was validated against a large-scale shaking table test. Seismic responses of GRS retaining walls are considerably affected by vertical excitation. Vertical seismic loading modified the vibration characteristics of GRS walls. Reinforcement load is well correlated with the horizontal Arias intensity at the wall top.